Банк: [роман-расследование] / Всеволод Данилов - Данилов Всеволод (Сделано в России, 2000)
Экземпляры: ф. 1 (20140121) / Инвентарный номер: 100471 / Цена: 40.00 / Авт.знак: Д 18 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6